Literature in English: evaluating its suitability for Semester 1, PISMP (Bachelor of Education Programme) TESL - Nil Farakh Sulaiman, (Pusat Perkembangan Pelajar ,U.K.M, 2015)
Literature seems to always be a course that most often befuddles rather than captivates student teachers of TESL at the Institutes of Teacher Education. Facing “literary inadequacy” due to lack of exposure to literary critical analysis at the upper secondary and preparatory levels aggravates the problem. Analysis of literary texts at these levels is merely highlighting the occurrences of basic literary devices in prescribed texts but the functions of why such devices are utilised by authors are not deeply explored by secondary school teachers. Hence, the suitability of offering a literature course at the beginning of an undergraduate programme was investigated, utilising the CIPP evaluation model developed by Stufflebeam (1971). 73 theory-based self-constructed items were administered to 120 respondents of three TESL cohorts via a cross-sectional survey research design. Reliability value for each construct using Cronbach Alpha was computed and the overall reliability value 0.959 was obtained, indicating that the research instrument was reliable to fulfil the purpose of the study. Findings and discussion underline the significance of offering the course in the first semester of TESL programme as well as the importance of learning literature in the 21st century.